2015
DOI: 10.1134/s1063776115040214
|View full text |Cite
|
Sign up to set email alerts
|

Structural modifications of graphyne layers consisting of carbon atoms in the sp- and sp 2-hybridized states

Abstract: A model scheme is proposed for obtaining layered compounds consisting of carbon atoms in the sp and sp 2 hybridized states. This model is used to find the possibility of existing the following seven basic structural modifications of graphyne: α , β1 , β2 , β3 , γ1 , γ2 , and γ3 graphyne. Polymorphic modifica tions β3 graphyne and γ3 graphyne are described. The basic structural modifications of graphyne contain diatomic polyyne chains and consist only of carbon atoms in two different crystallographically equiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 96 publications
2
25
0
2
Order By: Relevance
“…All calculations were performed using the 6-31G(d) basis set [48,49]. This level of theory B3LYP/6-31G (d) has been widely used for the study of allotropic forms of carbon, successfully predicting the experimentally observed geometries [18][19][20][21][22][23][24][25][26]35]. Frequency calculations were carried out at the same level of theory in order to confirm that the optimized structures correspond to a local minimum.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All calculations were performed using the 6-31G(d) basis set [48,49]. This level of theory B3LYP/6-31G (d) has been widely used for the study of allotropic forms of carbon, successfully predicting the experimentally observed geometries [18][19][20][21][22][23][24][25][26]35]. Frequency calculations were carried out at the same level of theory in order to confirm that the optimized structures correspond to a local minimum.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the IPR is not commonly satisfied with the small fullerenes, due to the possibility to form a great variety of isomers, since the small differences in formation energies of each isomer make difficult to identify [11][12][13][14][15][16]. Therefore, theoretical studies of all possible isomers that can be form with small fullerenes have been performed using molecular dynamics [17,18], semi-empirical [14,18,24] and DFT methods [12,13,15,16,[20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Однако впервые экспериментально синтезировать одну из структурных разновидностей графина -графдиин (graphdiyne) удалось только в 2010 [8]. В ряде недавних теоретических исследований была предложена модельная схема построения всех возможных структурных разновидностей графина в результатате трансформации структуры исходных графеновых слоев [9,10]. Для ряда графиновых слоев построенных при помощи этой модельной схемы на основе слоев графена L 6 и L 4-12 был выполнен расчет оптимальной структуры и свойств [9 -12].…”
Section: Introductionunclassified